2022
DOI: 10.1101/2022.09.16.508273
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The patterned assembly and stepwise Vps4-mediated disassembly of composite ESCRT-III polymers drives archaeal cell division

Abstract: ESCRT-III family proteins form composite polymers that deform and cut membrane tubes in the context of a wide range of cell biological processes across the tree of life. In reconstituted systems sequential changes in the composition of ESCRT-III polymers induced by the AAA ATPase Vps4 have been shown to remodel membranes. However, it is not known how composite ESCRT-III polymers are organised and remodelled in space and time in cells. Here, taking advantage of the relative simplicity of the ESCRT-III-dependent… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 60 publications
1
13
0
Order By: Relevance
“…Additionally, although monomers of different types share a similar molecular structure [2,5], polymers of different ESCRT-III monomers have been observed to have different shapes and different membrane binding interfaces, depending on their precise monomer composition [5,[12][13][14][15][16][17]. Therefore, as the copolymers change in composition, their geometry and mechanical properties are also expected to change, allowing the ESCRT-III to perform work on the membrane [8,[18][19][20][21]. The time ordering of this staged assembly-disassembly process is robust and is believed to progressively drive membrane deformation and scission in a variety of biological processes [9,17,18,22,23].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, although monomers of different types share a similar molecular structure [2,5], polymers of different ESCRT-III monomers have been observed to have different shapes and different membrane binding interfaces, depending on their precise monomer composition [5,[12][13][14][15][16][17]. Therefore, as the copolymers change in composition, their geometry and mechanical properties are also expected to change, allowing the ESCRT-III to perform work on the membrane [8,[18][19][20][21]. The time ordering of this staged assembly-disassembly process is robust and is believed to progressively drive membrane deformation and scission in a variety of biological processes [9,17,18,22,23].…”
mentioning
confidence: 99%
“…PHYSICAL REVIEW LETTERS 129, 268101 (2022) 268101-4 active energy supply; whereas in experiments, dynamic disassembly is only observed upon addition of ATPase Vps4, which unfolds monomers and extracts them from the filament [9,10,20,[30][31][32][33][34]. This led us to explore whether a Vps4-like activity that promotes stress-dependent polymer disassembly could aid the process.…”
mentioning
confidence: 99%
“…To further minimise photodamage, adapted acquisition schemes such as ResCUE 13 and DyMIN 14 can be applied. In our study, all selected objects were measured within a FOV of 2.5×2.5µm 2 , using a pixel size of 17×17nm 2 , while we obtained a resolution of around 30nm 15 (Fig. 7).…”
Section: Resultsmentioning
confidence: 99%
“…The archaea samples used for imaging in this work were prepared as described in Hurtig et al 15 . DNA was labelled with Hoechst and imaged in the 405nm channel.…”
Section: Methodsmentioning
confidence: 99%
“…It mediates the rupture and sealing of various cellular membranes, including those between the nuclear envelope and plasma membrane, and is released from the membrane in the final stage through the transient ATP-dependent reaction with other ESCRT proteins, facilitated by Vps4. Furthermore, several studies have shown that the ESCRT-III complex plays important roles in various biological processes, including cell division (Harker-Kirschneck et al, 2022;Hurtig et al, 2023), immune regulation (Li et al, 2022), and neurodegenerative diseases (Lee et al, 2007a;Han et al, 2012).…”
mentioning
confidence: 99%